2014
DOI: 10.1371/journal.pone.0110595
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies on the Reaction between Dicyanocobinamide and Hypochlorous Acid

Abstract: Hypochlorous acid (HOCl) is a potent oxidant generated by myeloperoxidase (MPO), which is an abundant enzyme used for defense against microbes. We examined the potential role of HOCl in corrin ring destruction and subsequent formation of cyanogen chloride (CNCl) from dicyanocobinamide ((CN)2-Cbi). Stopped-flow analysis revealed that the reaction consists of at least three observable steps, including at least two sequential transient intermediates prior to corrin ring destruction. The first two steps were attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Furthermore, an initial rate of 8 × 10 3 M −1 s −1 was found for the binding of HOCl to hemoglobin, further supporting the possibility of HOCl-mediated hemoglobin damage in a biological setting [ 12 , 43 ]. Similarly, an initial rate constant of 2 × 10 3 M −1 s −1 was found for the binding of HOCl to a vitamin B12 derivative [ 8 , 14 ]. In a previous study, 200 μM HOCl was found to react with and destroy the heme of hemoglobin in red blood cells [ 12 ].…”
Section: Hocl-associated Hemoprotein Heme Destructionmentioning
confidence: 86%
See 3 more Smart Citations
“…Furthermore, an initial rate of 8 × 10 3 M −1 s −1 was found for the binding of HOCl to hemoglobin, further supporting the possibility of HOCl-mediated hemoglobin damage in a biological setting [ 12 , 43 ]. Similarly, an initial rate constant of 2 × 10 3 M −1 s −1 was found for the binding of HOCl to a vitamin B12 derivative [ 8 , 14 ]. In a previous study, 200 μM HOCl was found to react with and destroy the heme of hemoglobin in red blood cells [ 12 ].…”
Section: Hocl-associated Hemoprotein Heme Destructionmentioning
confidence: 86%
“…Using a variety of biochemical, physiological, and kinetic techniques, it has been shown that melatonin ceases HOCl-mediated vitamin B12 derivative corrin destruction [ 8 , 14 ]. Vitamin B12 deficiency has been associated with several conditions related to memory loss, immune system disorders, aging, heart disease, male infertility, diabetes, sleep disorders, depression, mental disorders, and inflammation [ 71 ].…”
Section: Hocl Mediates Corrin Ring (Vitamin B12) Destructionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, utilizing rapid kinetic measurements, high‐performance liquid chromatography (HPLC), and mass spectrometric techniques, we have highlighted the mechanism through which HOCl mediates the destruction of the metal‐ion derivatives of tetrapyrrole macrocyclic rings such as hemoproteins and vitamin B 12 (VB 12 ) derivatives . We have shown destruction of cyanocobalamin (Figure A), a common pharmacological form of VB 12 , mediated by HOCl, resulted in the generation of toxic molecular products such as chlorinated derivatives, different degradation products of corrin, the organic ring system of cobalamin, release of the toxic blood agents (CN − /cyanogen chloride [CNCl]), and redox‐active free cobalt (Co) through the formation of chloro‐cyanocobalamin (Figure B) …”
Section: Introductionmentioning
confidence: 99%